2019
DOI: 10.1136/bmjopen-2018-027765
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of topical and ablative therapies in treatment of anogenital warts: a systematic review and network meta-analysis

Abstract: ObjectiveTo generate estimates of comparative clinical effectiveness for interventions used in the treatment of anogenital warts (AGWs) through the systematic review, appraisal and synthesis of data from randomised controlled trials (RCTs).DesignSystematic review and network meta-analysis of RCTs. Search strategies were developed for MEDLINE, Embase, the Cochrane Library and the Web of Science. For electronic databases, searches were run from inception to March 2018. The systematic review was carried out follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 43 publications
2
25
0
5
Order By: Relevance
“…Our results are in line with the NMA of Barton et al [13], which concluded that ablative techniques were superior. However, unlike us, Barton Unlike systematic reviews on AGW management [10,13,97], our NMA examined the efficacy of combination therapies, including ablative therapy ? imiquimod, cryotherapy ?…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are in line with the NMA of Barton et al [13], which concluded that ablative techniques were superior. However, unlike us, Barton Unlike systematic reviews on AGW management [10,13,97], our NMA examined the efficacy of combination therapies, including ablative therapy ? imiquimod, cryotherapy ?…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, RCTs comparing several major treatments for AGWs (cryotherapy [12] vs podophyllotoxin cream or gel, imiquimod vs TCA, CO 2 laser vs surgery or electrosurgery, etc.) are lacking [10,[13][14][15] and may never be performed (because they are costly, time-consuming, less attractive than new treatments, etc.). Reliable evidence on the comparative efficacy of these treatments is nevertheless needed to make informed clinical decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high risk of bias has been identified in RCTs of AGW treatments. This is largely explained by the fact that blinding of participants and care providers is difficult or impossible to achieve in the case of provideradministered treatments [4,5]. Although Pontini et al [1] ensured that the effectiveness of the nitrizinc complex solution and cryotherapy was evaluated by someone other than the physician administering treatment, lack of blinding may have resulted in the physician's lack of conviction in his or her own actions and poor adherence to trial protocol, placebo effects, or early patient withdrawal from the study [6].…”
Section: Dear Editormentioning
confidence: 99%
“…A high risk of bias has been identified in RCTs of AGW treatments. This is largely explained by the fact that blinding of participants and care providers is difficult or impossible to achieve in the case of provider-administered treatments [ 4 , 5 ]. Although Pontini et al .…”
Section: Digital Featuresmentioning
confidence: 99%